2017
DOI: 10.1097/01.aoa.0000511997.60775.68
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors for Preeclampsia Determined in Early Pregnancy: Systematic Review and Meta-Analysis of Large Cohort Studies

Abstract: (BMJ. 2016;353:i1753) Earlier studies have reported the effectiveness of aspirin in preventing preeclampsia in women considered to be at moderate to high risk of developing this disorder. This current study was a meta-analysis of cohort studies examining risk factors for preeclampsia with the goal of estimating early in pregnancy (≤16 wk gestation) a woman’s risk of developing preeclampsia based on the presence of absence of various risk factors. Three practical estimates were generated: the absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…The analysis test results showed no significant relationship between the history of IUGR and the incidence of preeclampsia (p value = 1.000). This was in line with what Bartsch et al 12 in a systematic review and meta-analysis that the relative risk for each risk factor is significantly greater than 1.0 except for historical IUGR. Health services for pregnant women, which were more easily accessed through the nearest public health center or other services, could increase maternal awareness of their pregnancy.…”
Section: Relation Of Previous History and Preeclampsia Incidencesupporting
confidence: 91%
See 1 more Smart Citation
“…The analysis test results showed no significant relationship between the history of IUGR and the incidence of preeclampsia (p value = 1.000). This was in line with what Bartsch et al 12 in a systematic review and meta-analysis that the relative risk for each risk factor is significantly greater than 1.0 except for historical IUGR. Health services for pregnant women, which were more easily accessed through the nearest public health center or other services, could increase maternal awareness of their pregnancy.…”
Section: Relation Of Previous History and Preeclampsia Incidencesupporting
confidence: 91%
“…Another research stated that the pooled unadjusted relative risk (RR) for maternal age over 35 years was 1.2 and for maternal age over 40 years was 1.5. It indicated an increase in risk with increasing age 12 . This can occur due to physiological changes in blood vessels 13 .…”
Section: The Relation Of Maternal Characteristic and Preeclampsia Incidencementioning
confidence: 97%
“…It has been widely believed that the risk of PE/PIH is increased in women treated with assisted reproductive technology, especially in frozen embryo transfer (FET) pregnancies. [54][55][56] However, evidence is limited on the predictive value of first-trimester serum activin A for PE/PIH in women receiving IVF treatment. In this study, we have found that first-trimester activin A level in IVF pregnancies with subsequent PE/PIH is comparable to those in normal IVF pregnancies despite a slightly higher activin A level has been detected in IVF pregnancies developing PE/ PIH, suggesting the difference between IVF and naturally conceived pregnancies should be noticed when using activin A to screen for hypertensive disorders in pregnancy in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…20 Infertility treatments in women with PCOS result in higher rate of multiple pregnancy, 4 which is a known risk factor for HDP in the general population. 17 Prior research reports that having family history of HTN and T2DM elevates the risk of HTN, T2DM and subsequently HDP. 42 Given that we excluded women reporting chronic HTN and T2DM, it is possible that women with a family history of HTN have significant underlying risk factors contributing to their increased risk of HDP.…”
Section: Re Sultsmentioning
confidence: 99%